2004
DOI: 10.1029/2002tc001402
|View full text |Cite
|
Sign up to set email alerts
|

Surface uplift, tectonics, and erosion of eastern Tibet from large‐scale drainage patterns

Abstract: A new regional compilation of the drainage history in southeastern Tibet suggests that the modern rivers draining the plateau margin were once tributaries to a single, southward flowing system which drained into the South China Sea. Disruption of the paleo‐drainage occurred by river capture and reversal prior to or coeval with the initiation of Miocene (?) uplift in eastern Tibet, including ∼2000 m of surface uplift of the lower plateau margin since reversal of the flow direction of the Yangtze River. Despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
715
2
14

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 760 publications
(804 citation statements)
references
References 44 publications
31
715
2
14
Order By: Relevance
“…The C1 calibration point is based on the fossil record of Bagarius yarrelli from the Pliocene (5.3-1.8 Ma ago) of the Siwalik Hills in India (Lydekker, 1886). C2 and C3 each represents an upper bound of 4 Ma, derived from the capture of the Tsangpo by the Brahmaputra River, which occurred prior to about this time (Clark et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…The C1 calibration point is based on the fossil record of Bagarius yarrelli from the Pliocene (5.3-1.8 Ma ago) of the Siwalik Hills in India (Lydekker, 1886). C2 and C3 each represents an upper bound of 4 Ma, derived from the capture of the Tsangpo by the Brahmaputra River, which occurred prior to about this time (Clark et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…The Qinghai-Tibet Plateau, especially, has experienced extremely intense uplift from around 1000 m to 4000-5000 m above sea-level (Chinese Academy of Sciences, 1980). These events have led to profound changes of the trajectories of major Chinese rivers (Chinese Academy of Sciences, 1980;Clark et al, 2004). In southern China, several important rivers, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Such a perspective is therefore still far from clear promoting us to pursue further studies of the molecular phylogenetics of the sisorid catfishes. It has long been recognized that paleo-drainages of major continental East Asian Rivers, draining the south-eastern Tibet plateau margin, differed markedly from their current drainage patterns (Brookfield, 1998;Clark et al, 2004;Gregory, 1925;Gregory and Gregory, 1923;Hallet and Molnar, 2001;Métivier et al, 1999;Seeber and Gornitz, 1983;Zeitler et al, 2001). In a recent study, Clark et al (2004) suggested that these rivers were once tributaries to a single southward flowing system, which drained into the South China Sea (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…3A). Subsequent reorganization into modern major river drainages was primarily caused by river capture and reversal events associated with the initiation of Miocene uplifts in eastern Tibet (Clark et al, 2004). Although large-magnitude tectonic shear, prompted by the Indian-Asian collision around the eastern Himalayan syntaxis (especially in the ''Three River'' area where the Salween, Mekong, and Yangtze rivers run parallel, see Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation